Saving Wallacetrigona incisa: Community-Led Conservation Integrating Science and Indigenous Knowledge in North Luwu’s Mountain Forests, Indonesia - Suhri, Andi Gita Maulidyah Indraswari (Jurnal Sylva Lestari, 2025)
Community-led conservation that integrates science and indigenous knowledge is vital for ensuring ecological sustainability and local stewardship in biodiversity protection. Wallacetrigona incisa, a stingless bee species endemic to Sulawesi, serves as a key pollinator in the mountain forests of North Luwu, Indonesia. However, its populations are increasingly threatened by deforestation, habitat fragmentation, and unsustainable harvesting methods, such as felling nest trees and discarding colonies after honey extraction. This study assessed the population status, identified key threats, and developed conservation strategies that integrate ecological science with traditional knowledge and active community participation. Methods included systematic field surveys, habitat suitability modeling using MaxEnt, satellite image analysis to detect changes in forest cover, and participatory approaches such as interviews and focus group discussions. Participatory GIS (PGIS) was used to involve communities in mapping and planning conservation priorities. The results show that destructive harvesting poses a severe threat to W. incisa, whereas sustainable practices support colony stability and enhance honey productivity. Economic dependence on honey harvesting is high, yet awareness of sustainable methods is limited. The indigenous mappurondo belief system, which protects sacred forest areas, offers a cultural foundation for community-based conservation. This study emphasizes the necessity of an integrated strategy that combines habitat protection, community capacity building, and the revitalization of traditional ecological knowledge. This study concludes that integrating scientific data, sustainable harvesting practices, and indigenous traditions can enhance colony survival and community livelihoods.  The results underscore the potential of inclusive conservation policies that bridge ecological and socio-economic objectives, offering a replicable model for tropical biodiversity conservation that aligns with local well-being. Keywords: conservation, endemic bee, indigenous knowledge, sustainability, Wallacetrigona incisa